Advancing Leadership in Public Healthcare: Beyond Crowded Hospitals and Labour Shortfalls - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Features a panel discussion on the Singapore ageing population and the expanding demand for healthcare by four public healthcare leaders, at the SMU-Singhealth Graduate Diploma in Healthcare Management and Leadership graduation ceremony.